Identifikasi Pemetaan Potensi Peternakan di Kabupaten Probolinggo - Rifky Aldila Primasworo; Fikka Kartika Widyastuti (Universitas Tribhuwana Tunggadewi Malang, 2018)
Probolinggo has good breeding potential in terms of natural resources and agro-ecosystems need to aquaculture farms are equipped with facilities and infrastructure, but it supported the availability of land pasture and forage availability of fodder. The development potential of the farm can stimulate the economy of a region-based agribusiness farms that are located in the region could walk properly and systematically. Region farms are breeding business district of existing or new location which has natural resources as needed for aquaculture farms agro-ecosystems incorporating livestock development infrastructure supported adequately by the availability of land or pasture and forage availability of fodder. The livestock sector development concept is intended to stimulate the economy of a region-based agribusiness farms that are located in the region can work well. In this study the early stages of identifying and mapping potential livestock production and provide guidance as well as strategy development potential of livestock in Probolinggo. The results of this study are expected to provide a general description of the location of the future development of the livestock area.